Intrinsic and Extrinsic Reading Motivation ‎among Tenth-Grade Students in Jordan and ‎their Relationship to some Variables - Al-Tawalbeh ‎, Ali; Bany Khaled, Ayat (Jordan Journal of Educational Sciences, 2023)
The study aimed to define the level of intrinsic and extrinsic reading motivation among tenth-grade students in Jordan and their relationship to some variables. The study sample consisted of 839 tenth grade students selected using the stratified cluster sampling method. To achieve the study objectives, a reading motivation scale was developed. The study results showed that the level of reading motivation among tenth-grade students was high, as extrinsic reading motivation to read came in first with a high level, followed by intrinsic reading motivation with a high level. The study found that there is a statistically significant relationship between father’s educational level and reading motivation among tenth-grade students, while there is no statistically significant relationship between mother’s educational level and reading motivation among tenth grade students. The study revealed a statistically significant correlation between academic achievement in Arabic and reading motivation among tenth grade students. The results found statistically significant differences in reading motivation among tenth grade students due to gender, in favor of females. In light of the results, some recommendations were provided